ZnO-Based Amperometric Enzyme Biosensors - Helong Jiang; Baoping Wang; Xiaobing Zhang; Zhiwei Zhao; Wei Lei (Sensors, 2010)
Nanostructured ZnO with its unique properties could provide a suitable microenvironment for immobilization of enzymes while retaining their biological activity, and thus lead to an expanded use of this nanomaterial for the construction of electrochemical biosensors with enhanced analytical performance. ZnO-based enzyme electrochemical biosensors are summarized in several tables for an easy overview according to the target biosensing analyte (glucose, hydrogen peroxide, phenol and cholesterol), respectively. Moreover, recent developments in enzyme electrochemical biosensors based on ZnO nanomaterials are reviewed with an emphasis on the fabrications and features of ZnO, approaches for biosensor construction (e.g., modified electrodes and enzyme immobilization) and biosensor performances.